Human anatomy. - Martini, Frederic H., 1947-; Tallitsch, Robert B., ....-; Timmons, Michael J., ....- (San Francisco (Cal.) : Benjamin Cummings, 2009)
Description With its clarity of presentation, vibrant art palette, new student and instructor media supplements, and expanded focus on clinical material, the Sixth Edition of the best-selling text for the one-semester Human Anatomy course is better than ever! This award-winning textbook features an atlas-style format to showcase the art program, which is known for its appropriately detailed anatomical illustrations and exceptionally clear photographs of tissues and cadavers. Time-saving study tools help students arrive at a complete understanding of human anatomy. Human Anatomy, Sixth Edition comes with a comprehensive media package, including the new Practice Anatomy Lab (PAL) 2.0 media program; the new 3D Anatomy Animations with Gradable Quizzes, the new 3D Animations of Origins, Insertions, Actions, and Innervations with Gradable Quizzesl; Media Manager 2.1, and an extensively updated and improved companion website. The Sixth Edition's expanded clinical coverage is exhibited through
An increased number of Clinical Notes and the addition of new Clinical Cases. Contents 1. Foundations: An Introduction to Anatomy 2. Foundations: The Cell 3. Foundations: Tissues and Early Embryology 4. The Integumentary System 5. The Skeletal System: Osseous Tissue and Skeletal Structure 6. The Skeletal System: Axial Division 7. The Skeletal System: Appendicular Division 8. The Skeletal System: Articulations 9. The Muscular System: Skeletal Muscle Tissue and Muscle Organization 10. The Muscular System: Axial Musculature 11. The Muscular System: Appendicular Musculature 12. Surface Anatomy and Cross-Sectional Anatomy 13. The Nervous System: Neural Tissue 14. The Nervous System: The Spinal Cord and Spinal Nerves 15. The Nervous System: The Brain and Cranial Nerves 16. The Nervous System: Pathways And Higher-Order Functions 17. The Nervous System: Autonomic Division 18. The Nervous System: General and Special Senses 19. The Endocrine System 20. The Cardiovascular System: Blood 21. The Cardiovascular
System: The Heart 22. The Cardiovascular System: Vessels and Circulation 23. The Lymphoid System 24. The Respiratory System 25. The Digestive System 26. The Urinary System 27. The Reproductive System 28. The Reproductive System: Embryology and Human Development
Keywords: Anatomie